Penerapan Model Decision Support System Dalam Penentuan Pemilihan Minat Siswa - Mutammimul Ula; Rizky Putra Phonna; Ilham Saputra; Suheri; Angga Pratama (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
Identification of the development of interests and talents is important to know the potential of students in choosing the right major. This is important in seeing the types of students' special interests and talents. This study aims to determine the development of special interests and talents in students based on students' abilities and intelligence. The criteria used in the selection are national exam scores, basic competency test scores, report cards, school final exam scores and combined scores. A combination of smart and saw methods to see the value of calculating the level of accuracy with the results of the analysis of each ranking. The results of testing the smart and saw method can be applied by comparing the data with a system that has been determined at the beginning by the school so that a good level of accuracy is obtained. Furthermore, Abdul's UN score is 6.00, Competency Test Value is 7.00, Report Report is 6.00, Uas Value is 9.00, Combined Value is 8.00 for the normalization matrix, 0.71, 1, 0.69, 1, 00 1.00 and the results of the SAW method. Abdu with a value of 4.28, Bahri with a value of 4.64, Wisma with a value of 4.65 and Izzah with a value of 4.51. for each student interest is determined by the school. The results of the Primary Determination Decision Support System to help schools make the best decisions by utilizing the process in student talent selection.